A review on fish lipid : composition and changes during cooking methods. - Moradi, Yazdan; Bakar, Jamilah; Motalebi, A. A.; Syed Muhammad, S. H.; Che Man, Yaakob (Taylor & Francis, 2011)
Fish lipids are known to be beneficial for human health since they are rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). This benefit can be affected by some processing or cooking methods. The effects of different cooking methods on lipid content and fatty acid composition of different fish species have been previously studied. In this article, the fish lipid characteristics and their changes during different cooking methods were reviewed. The fat content and fatty acid composition of fish vary according to the species, season, and environmental conditions. The fish lipid characteristics also change during different cooking processes. Frying generally gives higher changes in the fish lipid composition than other cooking methods. For example, frying results in higher losses of DHA and EPA (compared to other cooking methods). Further, the lipid changes occurring during frying depend on the fat content of the fish, the frying oil composition, and the type of frying technology.